Report on emerging foliar soft rot disease on ginseng Panax vietnamensis and the identification of Neocosmospora ipomoeae and Fusarium miscanthi as the causal pathogens - Hau T. Duong; Duong T. Pham; Van T. Pham; Anh H. Le; Toi D. Nguyen; Nam X. Nguyen; Chung T. Khuat; Hang T. Dinh (Journal of Plant Protection Research)
In the spring-summer season of 2022, a disease outbreak occurred in Kon Tum province, the native habitat of Panax vietnamensis var. vietnamensis (Ngoc Linh ginseng), affecting (scattered) a farming area of more than 50,000 ginseng plants. In relation to this a survey was conducted on a total area of 15 ha, covering ginseng farms in Kon Tum and some other main ginseng planting areas in Vietnam. Two main foliar diseases were recorded in the survey: a previously reported anthracnose disease and a new foliar soft rot disease that occurred with a disease incidence of 1–30% and 2–26%, respectively. The latter was not reported for other Panax ginseng varieties, but only for P. vietnamensis. Among 79 fungal strains isolated from infected leaves, two strains NL5 and KT2.1.2 were identified as true pathogens causing foliar soft rot disease according to the results of pathogenicity tests (following Koch’s postulates), which confirmed a disease index of 12% for both strains. Based on microscopic morphology and comparative analyses of ITS, TEF1, and BT2 sequences, the two strains were identified as Neocosmospora ipomoeae NL5 and Fusarium miscanthi KT2.1.2. The newly discovered foliar soft rot disease on ginseng P. vietnamensis and the associated pathogens N. ipomoeae and F. miscanthi reported in this study raised concern about measures that should be taken to control this disease on Panax ginseng.